Meta-analysis reveals that pollinator functional diversity and abundance enhance crop pollination and yield - B. A. Woodcock (Nature Portfolio, 2019)
Pollinator communities could have nuanced effects on crop yield depending on their species and functional trait compositions. Here, the authors use a meta-analysis to show that, in addition to pollinator abundance, functional trait divergence also positively impacts yield of oilseed rape crops.